Sea Shepherd's Strategic Opposition to Legalized Seal Hunting in Canada - Mulia, Anggarani (Department of International Relations, Universitas Brawijaya, 2025)
Seal hunting has been practiced by the Inuit people for centuries as a means of survival in icy regions with limited natural resources. The Inuit hunt seals because every part of the animal provides numerous benefits. Over time, seal hunting was also adopted by fishermen along the Canadian coast. The reason for this hunting, as carried out by the fishermen, was to preserve the hunting culture of the Inuit. However, the purpose of hunting shifted from subsistence to commercial aims. As the revenue generated from the sale of seal hunting products contributed significantly to Canada’s income, the Canadian government legalized seal hunting, which subsequently led to large-scale hunting. The legalization caused environmental crimes, as the number of hunted seals exceeded the quotass set by the Department of Fisheries and Oceans (DFO), and the hunting methods were often brutal. Consequently, Canada came under scrunity from environmental-focused international Non-Governmental Organizations (INGOs), one of which is Sea Shepherd. This article provides an overview of Sea Shepherd as an actor within the Transnational Advocacy Network (TAN) and its efforts to end the legalization of seal hunting in Canada. The initiatives undertaken by Sea Shepherd have led to positive outcomes, such as the cessation of seal hunting export-import activities to the European Union and better control over the number of seals being hunted.